PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 65 PEKANBARU - Mardiana, Mardiana; Munjiatun, Munjiatun; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is based on the percentation of numbers of students who reach minimum result level of 80 is still low as it is shown in the first mid-semester 2014-2015. There were only 8 students (40%) of 20 students who reach minimum result level and 12 students (60%) students who did not reach the minimum result level with the average of 66,4. The problem happened because teachers were seldom to use learning model in learning process in the classroom. Of the problem mentioned, it needs to conduct a classroom research control by applying learning model based on problem. The research is located in the State SD Negeri 65 Pekanbaru, Pekanbaru and the subject of the research is 20 students of grade 5, with 12 males and 8 females. The reasearch is conducted in two cycles. In collecting data, the researcher uses monitoring sheet of teachers’ and students’ activity and daily test sheets. The result of the observation shown that teachers and students’ activity have increased. Teachers’ activity on the first cycle is 66,66% with good category, means increase, and on the second cycle becomes 85,41% with excellence category. Students’ activity on the first cycle increase to become 62,5% with good category, and then increase to become 83,91% or excellence on the second cycle. The result of the research shown that the result of study of students increase, with the basic result average 66,75 not complete category increace to be 79 or complete category, and in the second cycle more increasing to be 87,5% or complete category. The completeness of the study of students on the first cycle shown that 75% students have reached the minimum result level as it is certain. On the second cycle, increase to be 90% sudents who reach minimum result level and the completeness percentation as it is certain. The explanation above shown that through applying learning based on problem will increase the result of the study matematical and natural sicences of grade 5 of State SD Negeri 65 Pekanbaru, Pekanbaru in the academic year of 2014-2015.Keywords: Learning based on problem, the result of study mathematical and natural Sciences.